Field pattern characteristics of GPR antennas - Millard, S. G. (Elsevier Science Ltd., 2002)
Sub-surface radar has become increasingly popular for carrying out completely non-invasive integrity tests on concrete structures. Commercial systems are available with a range of antenna frequencies that may be selected for an investigation. The choice of a particular antenna frequency is often a compromise between the physical size of the antenna and the penetration and resolution capabilities provided by the antenna. However, there is an interaction between a surface contact antenna and the substrate under investigation that will alter the field pattern being transmitted that may have significant implications for interpretation of results. An experimental programme is described in which the characteristics of commercially available 900 MHz and 1 GHz antennas are compared in air and when in contact with concrete and water surfaces, together with an emulsion used in previous studies to simulate the radar properties of concrete. Results are presented showing the influence of the material being measured upon the signal divergence. These effects are considered in terms of the practical implications for field-testing using radar.